THE INVISIBLE HAND PROGRAM BY PT PERTAMINA MOR IV TO EDUCATE AND INCREASE PUBLIC AWARENESS ON SUBSIDIZED 3KG LPG - Trishna Dewi Wulandari; Tri Nuraniwati (Profetik: Jurnal Komunikasi, 2023)
This study explores the Invisible Hand, a cyber public relations program conducted by the Communication, Relations and Corporate Social Responsibility Unit of PT Pertamina (Persero) MOR IV to educate and to increase public awareness on the provision of subsidized 3Kg LPG in Central Java dan Yogyakarta Special Region. Originally intended for lower income households and micro-small businesses, the subsidized LPG is also enjoyed by higher income households and businesses which result in the scarcity of the LPG. PT Pertamina (Persero) MOR IV held the Invisible Hand program by using other parties’ media to promote their mission. This study applied a qualitative research method by conducting participatory observation, interview and questionnaire for its data collection. It indicated that the Invisible Hand program was implemented through two strategies: social media campaigns and media relations. The social media campaigns were promoted by paid promotion through popular local Instagram accounts in Central Java and Yogyakarta Special Region, and the media relations were executed through focus group discussion (FGD) with local journalists. Positive awareness and responses from the public were proven by positive Instagram engagements. Through the media relations, a common understanding between PT Pertamina (Persero) MOR IV and the journalists was achieved, and the messages to educate the public were well-delivered by the media.